Thematic-Based Big Book Learning Media as a Facility of Visual Learning Styles for Students - Ela Risnaini; Zerri Rahman Hakim; M. Taufik (Universitas Pendidikan Ganesha, 2020)
The low use of innovative learning media by teachers at the elementary school level is a serious problem at this time. This study aims to develop a thematic-based big book media as a means of visual learning styles for students in grade IV elementary schools. This research was conducted in elementary schools in grade IV with a total of 20 students with details of 10 students on a limited trial. This model consists of 6 stages, namely problem analysis, data collection, product design, design validation, design revision, and product testing. The instruments used were questionnaire sheets for media validation by lecturers and teachers and student questionnaire sheets. Based on the data analysis, it can be concluded that the quality of the big book media developed is in the feasible category with a percentage of 80% from media experts, a very feasible category with a percentage of 88% from 2 material experts, and 93.33% from linguists. The response of students to the big book media in the trial with 10 respondents was 85.4% with the very good category. So it can be concluded that the use of the big book media is said to be feasible because it can overcome problems that exist in elementary schools.